2006
DOI: 10.1016/j.neuron.2006.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Odorant Receptor Map in the Mouse Olfactory Bulb: In Vivo Sensitivity and Specificity of Receptor-Defined Glomeruli

Abstract: Odorant identity is represented in the olfactory bulb (OB) by the glomerular activity pattern, which reflects a combination of activated odorant receptors (ORs) in the olfactory epithelium. To elucidate this neuronal circuit at the molecular level, we established a functional OR identification strategy based on glomerular activity by combining in vivo Ca(2+) imaging, retrograde dye labeling, and single-cell RT-PCR. Spatial and functional mapping of OR-defined glomeruli revealed that the glomerular positional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
185
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(207 citation statements)
references
References 51 publications
19
185
3
Order By: Relevance
“…Receptor affinities can be much lower in heterologous systems than in vivo (28)(29)(30), where expression of receptors and signaling components are presumably optimized. Nevertheless, the threshold of cadaverine detection by TAAR13c of 3 μM is very similar to in vivo thresholds observed for the intact olfactory system (6,31) and to thresholds measured for isolated olfactory sensory neurons (2).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor affinities can be much lower in heterologous systems than in vivo (28)(29)(30), where expression of receptors and signaling components are presumably optimized. Nevertheless, the threshold of cadaverine detection by TAAR13c of 3 μM is very similar to in vivo thresholds observed for the intact olfactory system (6,31) and to thresholds measured for isolated olfactory sensory neurons (2).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, particularly at the receptor level, have included olfactory concentrationresponse relationships (Abaffy T et al, 2006;Jacquier V et al, 2006;Kajiya K et al, 2001;Katada S et al, 2005;Oka Y et al, 2006;Pelz D et al, 2006;Shirokova E et al, 2005). Table 3 summarizes their characteristics and those of the present work.…”
Section: Vapor Concentration Range Issuesmentioning
confidence: 99%
“…(Studies where the odorant is presented indirectly in the liquid phase -and, often, quantified only in such phase -but where the tested species actually samples the vapor above the liquid do not constitute liquid phase presentations.) Notably, experiments within the same study (Oka Y et al, 2006) have shown that whereas delivery of the odorant as a vapor still needs to reach μM concentrations when the response is measured at the cell level (e.g., HEK293 or isolated olfactory sensory neurons: OSNs), it only needs to reach nM concentrations when the response is measured at the glomerular level. Thus, responses measured beyond the individual cell level, be it at the olfactory bulb (mouse) (Oka Y et al, 2006), the antennal lobe (fly) (Pelz D et al, 2006), or the integrated olfactory system (human) (this study; Cain WS et al, 2007b;Cometto-Muñiz JE et al, 2004;Wise PM et al, 2007), produce EC 50 s at or below the nM range.…”
Section: Vapor Concentration Range Issuesmentioning
confidence: 99%
See 2 more Smart Citations